2014
DOI: 10.1007/s11999-014-3918-x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Patients Undergoing Total Knee Arthroplasty: Do They Influence Hospital Costs and Length of Stay?

Abstract: Background Increasing national expenditures and use associated with TKA have resulted in pressure to reduce costs through various reimbursement cuts. However, within the arthroplasty literature, few studies have examined the association of medical comorbidities on resource use and length of stay after joint arthroplasty. Questions/purposes The purpose of this study was to examine the association between individual patient characteristics (including demographic factors and medical comorbidities) on resource all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 28 publications
7
41
0
1
Order By: Relevance
“…Given patients were interviewed within 3 months of the surgery, it was expected that physical limitations would emerge as a main activity barrier. Additionally, over 85% of TKA patients have comorbidities [36]; thus, it is likely that these other health issues may be contributing to the nonknee-related physical limitations. Many patients’ expectations regarding the timing of recovery and functional capabilities are high prior to the surgery and often go unmet.…”
Section: Discussionmentioning
confidence: 99%
“…Given patients were interviewed within 3 months of the surgery, it was expected that physical limitations would emerge as a main activity barrier. Additionally, over 85% of TKA patients have comorbidities [36]; thus, it is likely that these other health issues may be contributing to the nonknee-related physical limitations. Many patients’ expectations regarding the timing of recovery and functional capabilities are high prior to the surgery and often go unmet.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, there has been a considerable amount of progress in reducing the LOS [5] because many potential factors for prolonged LOS have been studied, including age, sex, comorbidities, weekend admission, the American Society of Anesthesiologists (ASA) classification, preoperative education, and the need for blood transfusion [6][7][8][9][10][11][12][13]. Additionally, with the introduction of fast-track protocols, which emphasize pain and blood management, limit perioperative complications, and promote postoperative early ambulation, the LOS has decreased dramatically without compromising functional recovery [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…22 Elsewhere, others have reported that patients with multiple comorbidities do have a longer LOS after knee surgery, and that diabetes was the second most common condition, increasing LOS by 20%. 20 Norris and Parker also have shown an increased risk of *The Chronic Disability Payment System model defines 2 severity levels for type 1 diabetes (High and Medium) and 2 levels for type 2 diabetes (Medium and Low). For cardiac and kidney comorbidities, there are 4 levels of severity.…”
Section: Discussionmentioning
confidence: 99%